Association Between Mode of Delivery and Incidence of Overactive Bladder (OAB) in Community Health Centers in Padang - Diniy Miftahul Muthmainah; Utama, Bobby Indra; Yetti, Husna (Fakultas Kedokteran Universitas Andalas, 2025)
Background: Overactive bladder (OAB) is a syndrome characterized by unstable bladder contractions and significantly impacts the quality of life. Risk factors such as age, pregnancy, and childbirth are often associated with lower urinary tract symptoms. While national epidemiological data on OAB in Indonesia is unavailable, a small study at a public health center in Padang revealed a high prevalence of OAB among pregnant women (97.14%). This study aims to analyze the association between mode of delivery and the incidence of OAB. Method: This study employed a cross-sectional design conducted at community health centers in Padang. Data were collected through structured interviews and medical records. The inclusion criteria were women aged 20–45 years who had experienced at least one delivery. OAB was assessed using the Overactive Bladder Symptom Score (OABSS). Statistical analysis was performed to determine the association between delivery methods (vaginal or cesarean) and the incidence of OAB. Result: Out of the total participants, 65.4% reported OAB symptoms. The incidence was significantly higher in women with a history of vaginal delivery compared to those with cesarean delivery (p < 0.05). Furthermore, age and parity were found to be contributing factors to OAB symptoms. Discussion: The findings suggest that the mode of delivery is associated with the incidence of OAB, with vaginal delivery posing a higher risk. These results underscore the importance of counseling pregnant women about potential long-term urinary health outcomes associated with childbirth techniques. Further studies with larger samples and more diverse populations are recommended to validate these findings. Keywords: overactive bladder, vaginal delivery, caesarean section